Somewhere Between Great Expectations and Disappointment... Some Reflections on Emotional Intelligence - Katarzyna Anna Knopp (University of Lower Silesia, 2014)
The article elaborates on the construct of emotional intelligence, wherein it focuses on both-explaining the causes of the enormous popularity of this concept and outlining the major issues and concerns associated with it. Presenting the basic assumptions of the ability model by Salovey and Mayer and the most popular mixed models (Goleman's and Bar-On's) has pointed out the huge differences in the adopted definitions and a proposed structure of emotional intelligence. The advantages and short comings of these models were described too. The article has also highlighted the problems associated with the measurement of emotional intelligence, as well as insufficient knowledge of its circumstances and dynamics of development. The reflection on the functional importance of emotional intelligence is a significant part of the article, which also attempted to confront popularizers' claims with available empirical data.